Studies in stamina of judoists (1) - Sasa, T.; Asami, T.; Kaneko, M. (Association for the Scientific Studies on Judo, Kodokan, 1969)
The interpretation of the term " stamina" differs according to the sport in question. The essential points of " stamina" required differ somewhat with the various kinds of sports, for example: a sport with a long duration (marathon, long distance running, long distance swimming, bicycle road race, etc.), a sport requiring and outburst of energy for a short duration (short distance running, short distance swimming, sumo, etc.), a match with an opponent and lasting for 3 to 6 minutes (Judo, wrestling, boxing, fencing, etc.) or a ball game requiring two opposing teams and lasting for a considerable length of time (soccer, volley ball, rugby, hockey, etc.). In other words, these may be divided into sports requiring stamina of the respiratory and circulatory systems, stamina of power, stamina of muscle strength, stamina of speed, or stamina of the nervous system. Prof. Ikai (University of Tokyo) holds the view that human reaction to muscular activity may be divided into aerobic and anaerobic reaction, and from this standpoint explains that, whereas in such sport as m arathon in which endurance is of primary importance (aerobic reaction), in the " last spurt" or in strenuous competitive sport in which an outburt of energy is required, an anaerobic reaction is necessary, and whether the athlete has stamina or not depends on whether he has this reserve energy. Prof. Fukuda defines stamina as "physical fitness having enough latent force which enables the athlete to hold out against odds" . In Judo, the problem of stamina was given only slight consideration until February 1963 when the Soviet Judo group visited Japan and showed very energetic bouts which aroused great interest in the cultivation of stamina. Also, results of various measurements of physical fitness of the Judo paticipants in the 1963 Olympic Games indicated that fitness indices of the Harvard step test and muscle endurance test, both considered as indices of stamina were comparatively low, attesting to the lack of stamina in these athletes (Measurements of physical fitness of Judo participants in the 1964 Olympic Games. Judo, October, 1963). Thereupon, it was thought that it would help considerably in training Judo athletes to investigate into the actual conditions of stamina required by the athletes, and the cause of the lack of stamina in these athletes.